PEMBUKTIAN TINDAK PIDANA KORUPSI INDONESIA DENGAN BELANDA: The Verification of Corruption Offenses in Indonesia and the Netherlands - Ratu, Gabriella Antonia; Kirana, Gandes Candra (Faculty of Law, Universitas Trisakti, 2025)
Corruption is a complex issue with wide-ranging impacts in various countries, including Indonesia and the Netherlands. This study aims to compare the regulations and proof mechanisms of corruption crimes in both countries. In Indonesia, proving corruption crimes involves the application of a reverse burden of proof, where the defendant must prove that their wealth was obtained legally. This contrasts with the general principle of criminal law, which places the burden of proof on the public prosecutor. In the Netherlands, the burden of proof remains with the public prosecutor, who must prove the defendant's guilt beyond a reasonable doubt. This study uses a normative juridical approach with qualitative analysis of secondary data from various legal sources. The findings indicate that despite the different approaches, both Indonesia and the Netherlands emphasize the use of valid evidence and fair trial processes. The reverse burden of the proof system in Indonesia shows a more aggressive effort in combating corruption but also poses challenges in implementation.